Participation in Social Media Health Groups for Exercise and Dietary Behaviours among Facebook and Instagram Users in Ghana MPhil Communication Studies - Ahiable, R. (University of Ghana, 2019)
This study adopts a mixed method approach to interrogate how social media is being used by individuals, both experts and non-experts in the promotion of diet and exercise. Using the social cognitive theory and the uses and gratifications theory as the theoretical framework, the study investigated how Ghanaians are using the Facebook and Instagram applications in their exercise and diet promotion behaviours. The objective of the study was to find out why people join these virtual communities to seek health information and the gratifications they seek from them. The study also looked to explore the kind of people who actively used these platforms and also sought to discover the self-efficacy levels of members of these social media health groups and the factors that motivate or demotivate their participation. Combining quantitative and qualitative data from survey and in-depth interviews respectively, information was gathered and analysed to explore the questions the study sought to answer. The study found that most participants in SMHGs are young females who join social media health groups (SMHGs) to lose or maintain weight in a cost-effective way. Additionally, findings also indicated that respondents wanted to broaden their dietary options and to discover where to find diet approved ingredients. In addition, the study found that accessing SMHG platforms have become somewhat habitual as members visit such pages at least twice daily. In terms of any link between participation and goal attainment, the study found that individuals who posted regularly, commented on the posts of others and engaged in live chats reported they achieved their objectives. Also, the study found that while self-efficacy to exercise was high among members of these groups, self-efficacy to diet was low. Positive comments and sharing of before and after posts motivated members to participate more, while insults and attacks demotivated participation.
MPhil. Communication Studies
Keywords: ICT; Health Delivery; Social Media; Ghana